2017
DOI: 10.3390/app7111120
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Hydrodynamic Performance of Typical Underwater Bionic Foils with Spanwise Flexibility

Abstract: Bionic foils are usually similar in shape to the locomotive organs of animals living in fluid media, which is helpful in the analysis of the motion mode and hydrodynamic mechanisms of biological prototypes. With the design of underwater vehicles as the research background, bionic foils are adopted as research objects in this paper. A geometric model and a motion model are established depending on the biological prototype. In the model, two typical bionic foils-a NACA foil and a crescent-shaped foil-are chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In addition, the thrust force and the wave power utilization coefficients of the flexible foil are 13% and 25% larger than those of rigid foil at ω 0 /ω f = 1 under waves. This phenomenon shows that flexible deformation can improve the propulsive performance of the foil, and this conclusion is in agreement with Zhou [17,18].…”
Section: Effect Of Wave Encounter Frequency On Foil Performancesupporting
confidence: 87%
“…In addition, the thrust force and the wave power utilization coefficients of the flexible foil are 13% and 25% larger than those of rigid foil at ω 0 /ω f = 1 under waves. This phenomenon shows that flexible deformation can improve the propulsive performance of the foil, and this conclusion is in agreement with Zhou [17,18].…”
Section: Effect Of Wave Encounter Frequency On Foil Performancesupporting
confidence: 87%
“…To advance this field further, Liu et al [62] and Zhou et al [63] utilized CFD methods to study self-propelled NACA0012 hydrofoil models and a biomimetic NACA0013 hydrofoil, while analyzing various factors affecting their propulsive performance.…”
Section: Biomimetic Hydrofoil-like Tail Fin Propulsionmentioning
confidence: 99%
“…Their predicted results revealed that the thrust and propulsion efficiency increased as a result of the passive deformation of fin rays. Zhou et al (2017) further studied a fish bodycaudal fin model and revealed that a faster swimming speed could be achieved for a fish model with a flexible caudal fin than that with a rigid one. It can thus be summarised from the above literature reviews that it is necessary to take into consideration the change in the fin shape while studying fish swimming behaviour.…”
Section: Introductionmentioning
confidence: 99%